Analisis Peran Guru sebagai Fasilitator dalam Pembelajaran Biologi di Era Digital - Alprianti Pare; Erni Murniarti (Jurnal Studi Guru dan Pembelajaran, 2024)
The development of digital technology has changed the role of teachers in education, especially in biology teaching. Teachers now act as facilitators who support students' exploration of knowledge through digital platforms. This research method uses a literature study to explore the role of teachers as facilitators in biology learning in the digital era by analyzing relevant literature such as books and journal articles, where the subjects of this study are Biology Teachers. This approach begins with determining inclusion and exclusion criteria, collecting relevant literature, summarizing the main findings from the sources reviewed, comparing findings from various sources, and compiling the results of the analysis. The research findings show that digital technologies such as simulations, virtual laboratories, and online resources increase students' interactivity and understanding of complex biological concepts. However, challenges include teachers' technological skills, infrastructure limitations, and resistance to change. Recommended strategies include technology training for teachers, investment in technological infrastructure, and creating a school culture that supports innovation. With this support, teachers can optimize digital technology to create more engaging and effective biology learning experiences, facilitate student engagement, and develop their critical thinking skills and creativity. This research is expected to have a significant impact on the development of biology learning strategies that are appropriate for the digital era.